Implementasi Nilai-Nilai Pancasila Perspektif Kiai Haji Achmad Siddiq Guna Menanamkan Pendidikan Karakter Siswa Sekolah Dasar - Lestari, Maghfirotul Firmaning; Ichsan, Maulana (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This research is motivated by the decline in character education due to cultural transformation and digitalization of the times. As a result, many children are less concerned about the history of Indonesia, the figure of the Hero, and the children's nationalist attitude will be weakened. Character education continues to be abandoned little by little because of the lack of influence from learning in instilling character education values ​​in students. Therefore, researchers are interested in bringing up the title "Implementation of Pancasila Values ​​from the Perspective of Kiai Haji Achmad Siddiq to Instill Character Education in Elementary School Students" because he is one of the figures who should be used as a direction or role model for students, a charismatic Kiai figure as well as a Hero who through his thoughts being able to become a person of merit can unite the relationship between the state and religion in the single principle of Pancasila. This research method is qualitative with literature review analysis techniques in the form of book instruments, journals and published digital articles. This research contains two problem formulations, namely what are the values ​​of the Pancasila from the perspective of Kiai Haji Achmad Siddiq and the second is how the implementation of the values ​​​​of the Pancasila from the perspective of Kiai Haji Achmad Siddiq can be instilled through character education in students at the elementary school level. The results of this study aim to analyze the Pancasila values ​​from the perspective of Kiai Haji Achmad Siddiq and find out the form of implementation of the Pancasila values ​​from the perspective of Kiai Haji Achmad Siddiq if instilled through character education in elementary school students.